Genome-Wide Identification and Expression Profiling of the SPL Transcription Factor Family in Response to Abiotic Stress in Centipedegrass - Dandan Kong; Maotao Xu; Siyu Liu; Tianqi Liu; Boyang Liu; Xiaoyun Wang; Zhixiao Dong; Xiao Ma; Junming Zhao; Xiong Lei (Plants)
SQUAMOSA promoter-binding protein-like (SPL) transcription factors play a critical role in the regulation of gene expression and are indispensable in orchestrating plant growth and development while also improving resistance to environmental stressors. Although it has been identified across a wide array of plant species, there have been no comprehensive studies on the SPL gene family in centipedegrass [Eremochloa ophiuroides (Munro) Hack.], which is an important warm-season perennial C4 turfgrass. In this study, 19 potential EoSPL genes in centipedegrass were identified and assigned the names EoSPL1-EoSPL19. Gene structure and motif analysis demonstrated that there was relative consistency among the branches of the phylogenetic tree. Five pairs of segmental duplication events were detected within centipedegrass. Ten EoSPL genes were predicted to be targeted by miR156. Additionally, the EoSPL genes were found to be predominantly expressed in leaves and demonstrated diverse responses to abiotic stress (salt, drought, glufosinate ammonium, aluminum, and cold). This study offers a comprehensive insight into the SPL gene family in centipedegrass, creating a foundation for elucidating the functions of EoSPL genes and investigating their involvement in abiotic stress responses.